PREVENTion and treatment of incontinence-associated dermatitis through a codesigned manual (PREVENT-IAD): a study protocol for a feasibility cluster randomised controlled trial with a nested process evaluation - Francesca Fiorentino; Christine Norton; Joanne M Fitzpatrick; Ruth Harris; Mandy Fader; Jan Kottner; Dimitri Beeckman; Sue Woodward; Tanya Graham; Peter Worsley; Sangeeta Sooriah; Chris Chatterton (BMJ Open)
Introduction Incontinence is commonly experienced by adults who receive care support in a residential facility or in their own home. These individuals are at risk of developing incontinence‐associated dermatitis (IAD), which is caused by prolonged and repeated exposure of the skin to urine or faeces. An IAD manual was developed providing an evidence-based clinical algorithm and an e-learning training programme for the prevention and treatment of IAD. The aim of the study is to establish the feasibility of conducting a definitive trial to examine the clinical and cost-effectiveness of the IAD manual. The objectives are to assess recruitment and attrition rates, acceptability of the IAD manual and intervention fidelity.Methods and analysis A feasibility cluster randomised controlled trial will be conducted in residential nursing homes and in the homes of people receiving formal care support in London and Hampshire, England. A total of six clusters including n=248 participants who are incontinent of urine, or faeces will be included. At each intervention site, care staff will be trained to implement the IAD manual over a 6-month period. Quantitative outcomes include IAD incidence and severity, IAD-related pain, satisfaction with care and mental health. A qualitative evaluation of care staff and care receivers’ experiences of participation will be conducted. Rates and proportions of each feasibility outcome will be described informing the sample size estimation for a definitive cluster randomised controlled trial. A thematic analysis of the qualitative data will be guided by a logic model detailing potential factors impacting on both the study methodology and adoption of the IAD manual into routine care.Ethics and dissemination The study received the approval of the Queens Square Ethics Committee Health Research Authority 23/LO/036, (Project ID 296167). Results will be disseminated through peer-reviewed open-access journals and international conferencesTrial registration number ISRCTN70866724.